Application EIMT Algorithm on Evaluation Method of English Multimedia Classroom Teaching Quality - Xie, Bin; Ma, Lili; Liu, Fengjun (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Multimedia teaching at this stage requires teachers to have specific technical and pedagogical skills when using multimedia teaching and be able to flexibly utilize multimedia tools for education. OBJECTIVES: The evaluation aims to provide a reference for teachers to improve their teaching and provide feedback on the quality of instruction for schools and educational management. METHODS: Based on the EIMT method, a method for evaluating the quality of English multimedia classroom teaching is proposed. The technique considers three factors, namely, teachers’ teaching ability, students’ learning, and course content, to comprehensively evaluate the quality of teaching. RESULTS: The final example verification of the selected cases shows that the evaluation system is reasonably constructed and the evaluation model is well applicable. CONCLUSION: Multimedia classroom teaching can improve students’ participation and enthusiasm. Multimedia teaching can stimulate students’ interest and curiosity through various forms, such as image, sound, and video, so they can actively participate in learning.